Physical Exercise in the Context of Air Pollution: An Emerging Research Topic - You, Yanwei; Wang, Dizhi; Liu, Jianxiu; Chen, Yuquan; Ma, Xindong; Li, Wenkai (Frontiers in Physiology, 2022)
Physical exercise (PE) brings physiological benefits to human health, paradoxically, exposure to air pollution (AP) is harmful. Hence, the combined effects of AP and PE are interesting issues worth exploring. The objective of this study is to review literature involved in AP-PE fields to perform a knowledge-map analysis and explore the collaborations, current hotspots, physiological applications and future perspectives. Herein, cluster, co-citation and co-occurrence analysis were applied using CiteSpace and VOSviewer software. The results demonstrated that AP-PE domains are springing up and in rapid growth since the 21st century. Subsequently, active countries and institutions were identified, and the productive institutions were mainly located in USA, China, UK, Spain and Canada. Developed countries seemed to be the major promoters. Additionally, subject analysis found that environmental science, public health and sports medicine were the core subjects and multi-dimensional communications were forming. Thereafter, a holistic presentation of reference co-citation clusters was conducted to discover the research topics and trace the development focuses. Youth, elite athletes, and rural population were regarded as the noteworthy subjects. Commuter exposure and moderate aerobic exercise represented the common research context and exercise strategy, respectively. Simultaneously, the research hotspots and application fields were elaborated by keyword co-occurrence distribution. It was noted that physiological adaptations including respiratory, cardiovascular, metabolic and mental health were the major themes; and oxidative stress and inflammatory response were the mostly referred mechanisms. Finally, several challenges were proposed, that are beneficial to promote the development of the research field. Molecular mechanisms and specific pathways are still unknown; and the equilibrium points and dose-effect relationships remain to be further explored. We are highly confident that this study provides a unique perspective to systematically and comprehensively review the AP-PE researches and its related physiological mechanisms for future investigations.